External evaluations and the Basic Education Development Index in the context of the New Public Management: An analysis of the Programa Escola de Gestores at the Federal University of Ouro Preto from the perspective of the basic agents in education - de Oliveira, Breynner Ricardo; Pena, Maria Tereza da Silva (Education Policy Analysis Archives, 2018)
This article analyzes the perceptions of teachers attended by the Programa Escola de Gestores at the Federal University of Ouro Preto in relation to external evaluations and the Index of Basic Education Development (Ideb). Teachers and members of the school management team are the grassroots public agents who translate and implement the public policies designed at the strategic level by the various governments. For Ideb, understanding how these subjects act and how they think is important in order to uncover how external evaluations have been processed in schools and what possible outcomes are produced there. The literature reveals that this indicator has promoted changes in daily school dynamics and at the level of education departments, often driven by accountability actions in a context of public policies of a managerial state. Sixteen interviews were conducted in eight public schools with the management team in the municipalities of Mariana, Ouro Preto, João Monlevade and Itabira (Minas Gerais). The analysis revealed that the external evaluations and Ideb have an inductive effect on the school, promoting the teachers' connection with the pedagogical project, increasing the number of pedagogical meetings and a concern with curricular planning. Interviews also revealed that such movements depend on the profile of school leaders. The involvement of the management teams is a central aspect for the professionals who work in them to commit to this process. On the other hand, the interviews showed that Ideb has become a regulatory instrument for educational evaluation policies, aimed at measuring results, which contributes to the generation of malaise between professionals and schools, revealing subtle and naturalized practices of accountability.